PHYSICAL TESTS OF ORGANIC INK BASED ON GUM ARABIC, GAMBIER, AND JANGGELAN LEAVES - Masthura, Masthura; Pasha, Ikhwani; Wulandari, Sri; Panjaitan, Hilwa; Ramadhani, Devi (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2024)
The basic color of ink is black, which contains carbon, making it easier for us to use natural elements around us as the raw material for making organic ink, and it is, of course, more cost-effective. One potential natural material that can be used as a color source to replace synthetic materials in ink production is gum arabic, gambier, and janggelan leaves. This study aims to determine the physical tests of organic ink made from gum arabic, gambier, and janggelan leaves based on the Indonesian National Standard (SNI) No 06-1567-1989. The physical tests conducted include density, viscosity, and color pigment tests. The results of testing the three materials used—gum arabic, gambier, and janggelan leaves—showed that gum arabic is the most optimal for making organic ink. This is evident from the test results, which showed a density of 1.076 g/cm³, a viscosity of 2.56 poise, and a deep black color pigment.